Information processing and management of uncertainty in knowledge-based systems. theory and foundations ; 17th International Conference, IPMU 2018, Cádiz, Spain, June 11-15, 2018, proceedings /: theory and foundations ; 17th International Conference, IPMU 2018, Cádiz, Spain, June 11-15, 2018, proceedings. Part II : (2018) - Unknown
No abstract available